Carbon Emission Disclosure: Analisis Tipe Industri dan Kepemilikan Institusional Pada Perusahaan Sektor Pertambangan Di Indonesia - Rita Eka Sari; Sari Mujiani; Efrinal (Relevan : Jurnal Riset Akuntansi, 2025)
This research aims to determine the influence of type of industry and institutional ownership on carbon emission disclosure among companies listed on the Indonesia Stock Exchange in the mining sector by analyzing their financial and sustainability reports for the period 2021-2023. The sample consists of 23 companies selected using purposive sampling. The data source is secondary data obtained from the official website www.idx.co.id. Data analysis was performed using multiple linear regression with the help of SPSS 26 statistical software. The results indicate that both industry type and institutional ownership have a significant positive effect on carbon emission disclosure. This means that as the disclosure of environmental costs increases, the realization of carbon emissions disclosure becomes more optimal, and as institutional ownership increases, the realization of carbon emissions disclosure also becomes more optimal.